(3YLGFH GdCNHGQ Yf eUQ GdCeUGQs - (3GdbGVj eYQhas
(3ChdgG (B:s
(3HMeOc Gddge hTcQc , hGSJOGeI PcQc hHYO agPg faNGJ bO SJfSeJ GdHGH GdChd ai PcQ eHOC GdScfi s
(3BNQgG (B:s
(3dHjc Gddge dHjc , hGdNjQ cdg ai jOjc , GbefG Gddge ebGe GdbHhd ai cd SDd hUdi Gdgd Ydi SjOfG eMeO s
(3HgG fXGe GdJYbjHIs
(3hjdGMX Cf GdeDda jfbd Yf GdebQjRis
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI LGeYI Gdedc YHO GdYRjR GdeQcRjI HLOIs
Keywords: (3GdJGQjNs